Foreign experience in organization of commercialization office (Journal of Economic Research & Business Administration, 2016)
Commercialization and usage of domestic scientific research results arevery important in the formation of an innovative economy. In this regard, itshould be noted that effective operation of innovation infrastructure facilities,and especially offices and centers of commercialization are necessary. Whenthe “National Agency for Technological Development» of Kazakhstan stoppedfunding commercialization offices, many of them either cut staff or stoppedtheir work. However, after the adoption of a new law in 2015, commercializationhas become one of the priorities of the universities and research institutes.Therefore, the question about how to effectively organize the work of thenewly created office of commercialization arises. This article discusses worldexperience in the organization of the offices and centers of commercialization.Also, the main functions of the office of commercialization, income distributionmechanism, and the requirements for personnel and indicators to assessperformance were analyzed. The article may be of interest to those involvedin the commercialization of scientific research in universities.
Keywords: commercialization office; commercialization of innovations; the mechanism of technology commercialization; foreign experience of commercialization.